A Probit Model and Probability of Monetary Policy Decision: Thailand Case - Suksawang, Varunya; Eamsopana, Pichit; Pinmanee, Pratya; Pattarabanjird, Surachai (Siam University Journal of Business Administration, 2022)
This paper created a probit model to test what were the important factors affecting the probability of making a monetary policy decision. It followed next to apply the model to forecast the probability of making a monetary policy decision under the given inflation and economic growth rates. The results indicated that the change in headline inflation rate had negative impact on the probability of making an easy monetary policy decision. In other words, if the size of change in headline inflation rate increased, the probability of an easy monetary policy decision would decrease. The finding of this study coincided with the economic concept because the easy monetary policy increases gross domestic product but at the same time puts upward pressure on general price level causing condition of inflation. The greater the change in headline inflation rate in size, inflation condition is even more intense. As a result, the probability of making a decision to implement an easy monetary policy is reduced.